Humanization of Logo as a Representation of Social Values in Halodoc - Tommi Tommi; Acep Iwan Saidi; Thirathep Chonmaitree; Mohamed Razeef Abdul Razak; Wegig Murwonugroho (JSW (Jurnal Sosiologi Walisongo), 2022)
In utilizing the Halodoc application, there is a communication gap between direct speech communication and communication through the application. This research attempts to examine this problem and propose an alternative solution in the form of emoji humanization through the qualitative method and Roland Barthes' semiotic approach. The result of the research shows that Heidy's emoji structure is indeed synonymous with the Halodoc logo. Meanwhile, according to the connotative analysis, the emoji visualization characters are identical to today's human characters. This character is characterized by expressions and facial expressions that look cheerful and friendly. This study concludes that there are several indicators of success in composing humanist emojis and still referencing the main logo identity. In the principle of emoji design, structurally it must be dominated by a shape similar to the original logo. The addition of mimics, expressions, limb movements, and body movements itself must represent the true expressions of humans who provide health-ordering services. Thus, emojis are more attractive, interactive, and communicative. This intimacy between users and humanist emojis may strengthen customer trust in the services.